Characteristics of post-parturition areas of moose in northeast Minnesota - McGraw, Amanda M; Moen, Ron; Schrage, Mike (Lakehead University, 2012)
Habitat used in the three to four weeks after parturition could be important to calf survival. Newborn calves are vulnerable to predation, and the cow needs adequate forage reserves during the period when calf mobility is limited. Radio collared cows were located by visual observation from helicopters between May 21 and June 5 from 2004-2007. A post-parturition area was defined as 100 ha surrounding the cow/calf location. We determined cover type composition in post-parturition areas compared to the 95% kernel home ranges of moose. Buffers of 5, 10, 25, and 50 ha were created around post-parturition areas to determine cover type composition at smaller spatial scales. Post-parturition areas were also compared to equivalent areas surrounding cows without calves. Post-parturition sites had more lowland conifer and shrubland or regenerating/young forest cover types than random locations within the home range. Cows with calves selected areas with larger proportions of lowland conifer, shrublands, and regenerating forests than did cows without calves. These cover types could have been used for cover and for foraging, respectively. There was no difference in the amount of water available in post-parturition areas (3.5% ± 0.8) when compared to home ranges (3.5% ± 0.8). Distances between consecutive post-parturition locations (1.7 ± 0.4 km) were less than expected when compared to distances to random points within the home ranges (3.3 ± 0.4 km).